Diagnostic and prognostic value of preoperative combined GFAP, IGFBP‐2, and YKL‐40 plasma levels in patients with glioblastoma. Issue 24 (19th August 2014) - Gállego Pérez‐Larraya, Jaime; Paris, Sophie; Idbaih, Ahmed; Dehais, Caroline; Laigle‐Donadey, Florence; Navarro, Soledad; Capelle, Laurent; Mokhtari, Karima; Marie, Yannick; Sanson, Marc; Hoang‐Xuan, Khê; Delattre, Jean‐Yves; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Circulating proteins released by tumor cells have recently been investigated as potential single surrogate biomarkers for glioblastoma multiforme (GBM). The aim of the current hypothesis‐generating study was to evaluate the diagnostic and prognostic role of preoperative insulin‐like growth factor‐binding protein 2 (IGFBP‐2), chitinase‐3‐like protein 1 (YKL‐40), and glial fibrillary acidic protein (GFAP) plasma levels in patients with GBM, both as single markers and as a combined profile. METHODS Plasma samples from 111 patients with GBM and a subset of 40 patients with nonglial brain tumors were obtained preoperatively. Plasma from 99 healthy controls was also analyzed. IGFBP‐2, YKL‐40, and GFAP levels were determined using enzyme‐linked immunoadsorbent assay tests. Their association with histological and radiological variables was assessed. RESULTS Circulating levels of all 3 proteins were found to be significantly higher in patients with GBM compared with healthy controls (P < .01). Only YKL‐40 and GFAP were found to demonstrate significant differences between patients with GBM and nonglial brain tumors (P = .04). GFAP was undetectable (<0.02 ng/mL) in all patients without GBM. A receiver operating characteristic analysis accounting for a 2‐step diagnostic procedure including the 3 biomarkers afforded an area under the curve of 0.77 for differentiating patients with GBM from those with nonglial brain tumors. There was a significant correlation between tumor volume and plasma IGFBP‐2 level (Spearman Rho correlation coefficient, 0.22; P = .025) and GFAP (Spearman Rho correlation coefficient, 0.36; P < .001) among patients with GBM. Preoperative plasma IGFBP‐2 levels were found to be independently associated with worse overall survival among patients with GBM (hazard ratio, 1.3; P = .05). CONCLUSIONS A combined profile of preoperative IGFBP‐2, GFAP, and YKL‐40 plasma levels could serve as an additional diagnostic tool for patients with inoperable brain lesions suggestive of GBM. In addition, IGFBP‐2 levels appear to constitute an independent prognostic factor in patients with GBM. Cancer 2014;120:3972–3980. © 2014 American Cancer Society.